The Intersection of the Socially Embedded Economy and Participatory Development Projects in Eastern Highlands Province, Papua New Guinea - McKellar, Jennifer A. (Curtin University, 2024)
This research examines the features of social embeddedness which shape the outcomes of Development projects in a coffee farming community in Eastern Highlands Province, Papua New Guinea. Recognition of the ways in which the village economy is socially embedded, and the ways in which actors, institutions, and Development projects intersect to produce change, can facilitate project design which better meets both the economic and social needs of community participants.